2017
DOI: 10.3390/molecules22040567
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sample Size to Assess the Genetic Diversity in Common Vetch (Vicia sativa L.) Populations Using Start Codon Targeted (SCoT) Markers

Abstract: Common vetch (Vicia sativa subsp. sativa L.) is a self-pollinating annual forage legume with worldwide importance. Here, we investigate the optimal number of individuals that may represent the genetic diversity of a single population, using Start Codon Targeted (SCoT) markers. Two cultivated varieties and two wild accessions were evaluated using five SCoT primers, also testing different sampling sizes: 1, 2, 3, 5, 8, 10, 20, 30, 40, 50, and 60 individuals. The results showed that the number of alleles and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Cluster analysis based on these traits grouped the genotypes into 8 separate clusters. CHAI et al (2017) investigate the optimal number of individuals that may represent the genetic diversity of a single population, using Start Codon Targeted (SCoT) markers. Two cultivated varieties and two wild accessions were evaluated using five SCoT primers, also testing different sampling sizes: 1, 2, 3, 5, 8, 10, 20, 30, 40, 50, and 60 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster analysis based on these traits grouped the genotypes into 8 separate clusters. CHAI et al (2017) investigate the optimal number of individuals that may represent the genetic diversity of a single population, using Start Codon Targeted (SCoT) markers. Two cultivated varieties and two wild accessions were evaluated using five SCoT primers, also testing different sampling sizes: 1, 2, 3, 5, 8, 10, 20, 30, 40, 50, and 60 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The hierarchical cluster analysis showed that the rye genotypes were divided into 2 main clusters. Chai et al (2017) investigate the optimal number of individuals that may represent the genetic diversity of a single population, using Start Codon Targeted (SCoT) markers. Two cultivated varieties and two wild accessions were evaluated using five SCoT primers, also testing different sampling sizes : 1, 2, 3, 5, 8, 10, 20, 30, 40, 50, and 60 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The non-uniform genetic distribution of cercariae among snails implies that sample size of snail hosts would affect the allele distribution of the cercaria suprapopulation (cercariae from all snails). Na, the basic index for indicating gene abundance of a population [45,46], was further evaluated for each locus in different cercariae subsets by selecting different numbers of snails randomly. Snails were selected randomly at each given number of snails, which was set from 1 to maximum in each group using the base function sample in R, with 100 replicates.…”
Section: Allele Distribution For Cercaria Subsets From the Different mentioning
confidence: 99%